The study of underwriting profitability for non-life insurance company - Dechkhong, Adipa; Skulpakdee, Wanrudee (Journal of Applied Statistics and Information Technology, 2022)
The objective of this study is to analyze the underwriting profitability of non-life insurance companies. In the first part, the expense ratio is analyzed by classifying the non-life insurance companies into 3 groups, i.e., the company with high, medium and low expense ratios. Then, in the next part, the probability distribution function of loss ratio for each group is analyzed. It was found that the appropriate probability distribution function of loss ratio for the company groups with medium and low expense ratio is the normal mixture distribution. The appropriate probability distribution function of loss ratio for the high expense ratio company group is the normal distribution. Then the researcher analyzed the probability of underwriting profit margin. The result is that a non-life insurance company with high, medium and low expense ratio has probability of underwriting profit of 0.1211, 0.1080 and 0.8920 respectively.